PUNK! : Las Américas edition - Rodríguez-Ulloa, Olga, editor; Quijano, Rodrigo, editor; Greene, Shane, 1971- (Global punk, 2021)
A critical refashioning of punk to suggest it emerges from within the long-term historical experience of las Américas in all their plurality. A collage-like juxtaposition of punk perspectives from across the entire hemisphere and via divergent contributions. 71 b/w illus.